(untitled) (European Journal of Pure and Applied Mathematics, 2019)
This paper presents numerical solution of some nonlinear degenerate parabolic equations arising in the spatial diÂ¤usion of biological populations. The SBA method based on combination of Adomian decomposition method, principle of Picard and successive approximations is used for solving these equations. The analytical obtained solutions show that the SBA method leads to more accurate results.